Experience, narrative, and criticism in ancient Greece: under the spell of stories - Grethlein, Jonas; Huitink, Luuk; Tagliabue, Aldo (Oxford University Press, 2020)
Drawing on cognitive approaches to literary studies, this volume pursues a new approach to ancient Greek narrative that transcends the taxonomies of structuralist narratologies, deploying concepts such as immersion and embodiment in order to establish a more comprehensive understanding of ancient Greek narrative and ancient reading habits.
This edition previously issued in print: 2019. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on January 13, 2020)
Keywords: Aufsatzsammlung; Erzähltheorie; Literatur; Griechisch